Antiseptic susceptibility profiles of canine pyoderma-associated staphylococci in Japan: first identification of plasmid-borne smr in Staphylococcus coagulans - Tsunoi, Manami; Takiguchi, Manabu; Ashida, Emi; Harada, Kazuki; Iyori, Keita; Shimizu, Koki (Frontiers in Veterinary Science, 2025)
IntroductionInternational guidelines recommend the use of antiseptics, such as chlorhexidine, to treat canine pyoderma. However, data on the antiseptic susceptibility of its primary causative agents, Staphylococcus pseudintermedius and S. coagulans, in Japan are limited.MethodsWe performed antiseptic susceptibility testing and polymerase chain reaction (PCR) screening for antiseptic resistance-associated genes in these species. In addition, hybrid genome sequencing was conducted for a resistant isolate to investigate the genetic context of resistance genes.ResultsMost isolates exhibited low minimum inhibitory concentrations for the tested antiseptics, although some inter-strain variations were observed. One S. coagulans isolate (SC18) was identified as smr-positive, representing only the second global report and the first from Japan. Phylogenetic analysis using publicly available genome data revealed that SC18 belongs to the major lineage of S. coagulans. Hybrid genome sequencing further demonstrated, for the first time, that smr in S. coagulans is plasmid-borne. Notably, this plasmid was also identified in a human-derived S. epidermidis strain (KSE124-2) in Japan, suggesting plasmid-mediated interspecies transmission between humans and companion animals.DiscussionThese findings highlight the need for continued surveillance of antiseptic resistance-associated genes, which may contribute to reduced phenotypic susceptibility and pose a potential public health concern.